Iringan Karawitan Pergelaran Wayang Golek Menak Yogyakarta Versi Ki Sukarno - Aji Santoso Nugroho (Wayang Nusantara: Journal of Puppetry, 2019)
This article aims to describe the musical accompaniment in the Menak Sukarno Golek Golek performance by Ki Sukarno. Musicology analysis is done using karawitan to reveal the structure, shape, workmanship, and function of karawitan in Ki Sukarno’s Menak Yogyakarta Golek Puppet show. From the observations of Ki Sukarno’s performance, it was concluded that the accompaniment of Menak Puppet Golek music used in the performance was basically not much different from the wayang kulit of Yogyakarta puppet. The difference between the two lies in the laya or rhythmic dish and the obstacle pattern, namely the wayang motion, the ater open the playon and the playon level. Laya or rhythm used refers to dance music and the pattern of resistance. This is because in the Menak Puppet Puppet contains elements of dance movement vocabulary. The performances of Menak Golek Puppet have a standard composition as accompaniment, namely the Gending Goal of Kabor Topèng, Orange Flower Sifter, Playon Kembang Jeruk, Playon Gégot, and Playon Gambuh. Karawitan in the performance of Menak Golek Puppet serves as a confirmation of scene changes, emphasizes the atmosphere of the scene, reinforces dramatic elements, emphasizes the character, and reinforces the character of puppet movements. The presentation structure of Menak Yogyakarta Golek Puppet refers to the structure of Purwa Yogyakarta Puppet Leather, both from the structure of the division of the scene, to the use of gamelan which only uses sléndro tunings. The element that  distinguishes it is only found in the scene ajon-ajon or majeng beksa, namely the motion of dance before committing a war and a fierce war scene. Artikel ini bertujuan mendeskripsikan iringan karawitan dalam pergelaran Wayang Golek Menak Yogyakarta versi Ki Sukarno. Analisis musikologi garap karawitan digunakan untuk mengungkap struktur, bentuk, garap, dan fungsi karawitan dalam pertunjukan Wayang Golek Menak Yogyakarta versi Ki Sukarno. Dari pengamatan terhadap pergelaran Ki Sukarno didapatkan kesimpulan bahwa iringan karawitan Wayang Golek Menak yang digunakan dalam pergelarannya pada dasarnya tidak berbeda jauh dari karawitan Wayang Kulit Yogyakarta. Perbedaan dari keduanya terletak pada sajian laya atau irama dan pola kendhangan yaitu ater-ater gerak wayang, ater-ater buka playon dan suwuk playon. Laya atau irama yang digunakan mengacu pada karawitan tari dan pola kendhangan. Hal ini dikarenakan dalam Wayang Golek Menak terkandung unsur vokabuler gerak tari. Pergelaran Wayang Golek Menak mempunyai gending baku sebagai iringan yaitu Ketawang Gending Kabor Topèng, Ayak-ayak  Kembang Jeruk, Playon Kembang Jeruk, Playon Gégot, dan Playon  Gambuh. Karawitan dalam pergelaran Wayang Golek Menak berfungsi sebagai penegas pergantian adegan, penegas suasana adegan, penegas unsur dramatik, penegas karakter tokoh, dan penegas karakter gerak wayang. Struktur penyajian Wayang Golek Menak Yogyakarta mengacu pada struktur Wayang Kulit Purwa Yogyakarta, baik itu dari struktur pembagian adegan, sampai penggunaan gamelan yang hanya  menggunakan laras sléndro. Unsur yang membedakannya hanya terdapat pada adegan ajon-ajon atau majeng beksa, yaitu gerak tarian sebelum melakukan perang dan adegan perang gecul.